Literature Review: The Role of RET Gene Mutations in The Emergence of Hirschsprung Disease - Azalia, Salsa Novela; Ahda, Yuni (Jurnal Biologi Tropis, 2024)
Hirschsprung’s disease is a congenital condition characterized by a failure of nerve function along the gastrointestinal (GI) tract, resulting in the absence of enteric ganglia in the most distal segment of the colon. Although the prevalence rate is 1:5000 babies born, Hirschsprung’s disease can have a significant impact on patients, especially in terms of quality of life. One of the main genetic factors often associated with the etiopathogenesis of Hirschsprung’s disease is the RET gene. This study aims to provide scientific insight into advances in the understanding of genetic variants associated with RET gene mutations and their role in causing Hirschsprung disease. The research design used was literature review, articles were collected based on sources derived from Google Scholar, PubMed, and EMBASE which included national and international journals published in the last 10 years. Based on the articles collected, it was found that the RET gene is essential for the growth, migration, and maturation of precursor cells into functional neurons. Mutations in the RET gene can interfere with the normal formation and function of nerve cells, leading to symptoms typical of Hirschsprung’s disease.